MEMBANGUN KARAKTER RELIGIUS MELALUI KURIKULUM MERDEKA PAI: : KAJIAN DESAIN, STRATEGI, DAN IMPLEMENTASI - Neng Sufia; Nasrun Harahap (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2025)
The Merdeka Curriculum for Islamic Religious Education (PAI) is an innovation within the Indonesian education system aimed at shaping students to be religious, virtuous, and have strong character in accordance with the Pancasila Student Profile. This curriculum is designed to be flexible, student-oriented, and to promote active, contextual, and meaningful learning. This study aims to describe the design of the Merdeka Curriculum based on educational levels, from primary to upper secondary education, by taking into account the developmental characteristics of students at each stage. The research employs a qualitative approach using the literature review method. The results show that the Merdeka Curriculum for PAI is structured to develop students who are religious, of good character, and prepared to face contemporary challenges, grounded in Islamic values and the Pancasila Student Profile. With its student-centered, flexible, and integrative learning principles, this curriculum allows for innovative approaches such as project-based learning, collaborative learning, and the use of technology. The curriculum structure is adjusted according to the educational level, from basic introduction at the SD/MI level to theological studies and contemporary issues at the SMA/MA level.